2011
DOI: 10.1007/s10120-011-0034-4
|View full text |Cite|
|
Sign up to set email alerts
|

p53 codon 72 polymorphism in patients with gastric and colorectal cancer in a Korean population

Abstract: Background The common p53 codon 72 polymorphism has been investigated as a risk factor for cancer in different populations; however, the results have been inconsistent. This study investigated the risk of developing gastric or colorectal cancer associated with the p53 codon 72 polymorphism in a Korean population. Methods We conducted a large-scale case-control study that included 2,213 gastric cancer patients; 1,829 colorectal cancer patients; and 1,700 healthy controls. Genotyping was performed with real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 29 publications
0
19
0
2
Order By: Relevance
“…Yet, no association was observed with TP53 c.215G>C, p. (Arg72Pro) SNP and the risk of bladder [41] and cervical carcinomas [42] in Moroccan population. Numerous studies have reported a significant association between TP53 c.215G>C, p. (Arg72Pro) polymorphism and the development of other malignancies [43][44][45][46]. However, this association was not observed in many other studies [47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 56%
“…Yet, no association was observed with TP53 c.215G>C, p. (Arg72Pro) SNP and the risk of bladder [41] and cervical carcinomas [42] in Moroccan population. Numerous studies have reported a significant association between TP53 c.215G>C, p. (Arg72Pro) polymorphism and the development of other malignancies [43][44][45][46]. However, this association was not observed in many other studies [47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, the results reported thus far have been inconsistent, and several studies have mainly included patients with sporadic CRC [11, 12, 13, 14, 15, 16]. Talseth et al reported that TP53 polymorphisms were not associated with CRC development in the Australian and Polish Lynch syndrome populations [17].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first description by Krontiris in 1985 that the polymorphisms of the RAS gene can be used to assess the risk of oncogenesis [3], more studies have begun to demonstrate associations between the polymorphisms and gastric cancer susceptibility, including oncogenes [4], antioncogenes [5], [6] and immunomodifier genes [7], [8]. It has also been suggested that genetic susceptibility genes, especially genes for metabolic enzymes, may confer a risk for the development of gastric cancer [9][11].…”
Section: Introductionmentioning
confidence: 99%